IMPLEMENTASI MODEL LEARNING TOGETHER UNTUK MENINGKATKAN KETERAMPILAN SOSIAL - Renni Suryani; Sudjarwo Sudjarwo; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2020)
This research aims to determine differences in social skills of students before andafter the application of learning together learning models, class differences using models with those who do not, and the effectiveness of learning together models in social studies learning to improve social skills in students. The research method used was an experimental research with a randomized control-group pretest-posttest design. The population of this study was grade VII students of SMP Negeri 34 Bandar Lampung. The results of this experimental study concluded that, (1) There were differences in social skills between before the application of the learning model together with after the application of the model in social studies subjects; (2) There are differences in social skills between classes with the application of learning together models with classes without the application of learning together models; (3)Learning together model is effective to improve social skills.Penelitian ini bertujuan untuk mengetahui perbedaan keterampilan sosial siswa sebelum dan setelah penerapan model pembelajaran learning together, perbedaan kelas menggunakan model dengan yang tidak, serta efektivitas model learning together dalam pembelajaran IPS untuk meningkatkan keterampilan sosial pada siswa. Metode penelitian yang digunakan adalah penelitian eksperimen (Experimental Research) dengan jenis desain rancangan Randomized control group pretest-postest design. Populasi penelitian ini adalah peserta didik kelas VII SMP Negeri 34 Bandar Lampung. Hasil penelitian eksperimen ini menyimpulkan bahwa, (1) Ada perbedaan keterampilan sosial antara sebelum penerapan model learning together dengan setelah penerapan model pada mata pelajaran IPS; (2) Ada perbedaan keterampilan sosial antara kelas dengan penerapan model learning together dengan kelas tanpa penerapan model learning together; (3) Model learning together efektif untuk meningkatkan keterampilan sosial siswa kelasKata kunci: Penelitian Eksperimen, Model Learning Together, Keterampilan Sosial.